Sexualities, teenage pregnancy and educational life histories in Portugal: experiencing sexual citizenship? - Laura Fonseca (2012)
This article focuses on Portuguese working-class teenage girls' voices and experiences concerning sexuality and pregnancy. Within a sociological, feminist and educational framework, it explores the girls' perspective on sexual and intimate citizenship as evidence of fairer forms of regulation of teenage sexualities. Through building life histories of three pregnant and teenage mothers, this article aims to understand how girls rehearse and live out their sexualities and pregnancies as well as listen to their voices and recognise their demand for inclusion and respect. Gender power relations emerge as central in configuring girls' pathways and shed light on youth pregnancy.